Five Layers Aurivillius Phases Pb2-xBi4+xTi5-xMnxO18: Synthesis, Structure, Relaxor Ferroelectric and Magnetic Properties - Zulhadjri Zulhadjri; B. Prijamboedi; A. A. Nugroho; N. Mufti; Ismunandar Ismu (Institute for Research and Community Services (LPPM) ITB, 2011)
Synthesis of five layers Aurivillius phases, Pb2-xBi4+xTi5-xMnxO18 (0